Green, Dividend, and Value: Three Pillars of Corporate Success - Sri Ningsih; Fitri Noviyanti; Marwah abdulkareem (Journal of Accounting and Auditing, 2026)
Purpose – This study aims to examine the effect of green accounting, dividend policy, and profitability on firm value in energy sector companies listed on the Indonesia Stock Exchange during the period 2022–2024. Design/methodology/approach – This study employs a quantitative approach using panel data analysis. The sample consists of 44 energy sector companies selected through purposive sampling based on the availability of complete annual and sustainability reports, resulting in 132 firm-year observations. Data were analyzed using panel regression techniques, including the Common Effect Model (CEM), Fixed Effect Model (FEM), and Random Effect Model (REM). The most appropriate model was selected using the Chow test and Hausman test. Data processing was conducted using EViews 9 software.  Findings – The results indicate that green accounting, dividend policy, and profitability have positive coefficient directions toward firm value. However, based on the selected Random Effect Model, these variables do not have a statistically significant effect on firm value. This finding suggests that sustainability practices and traditional financial indicators have not yet become primary determinants of firm value in the Indonesian energy sector. Research limitations/implications – This study is limited by the relatively small sample size due to incomplete sustainability reporting among energy companies. The findings imply that greater transparency and higher-quality environmental disclosure are needed for sustainability practices to be more fully reflected in firm valuation. Future research is encouraged to extend the observation period, include additional sectors, and apply alternative measurements of green accounting. JEL: G32 , G35, M41 , Q56